From the Index to Akhmatova’s Notebooks: Genrikh Yagoda - Roman D. Timenchik (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The article from the author's cycle “From the Index to Akhmatova's Notebooks” (published in various periodicals) demonstrates the attempt of an extensive commentary on Akhmatova's working notes, organized around the characters present on the pages of her notebooks, a kind of free Akhmatova encyclopedia, where different periods of her long life are combined in the onomasticon. A comment of this kind snatches out representative fragments of Akhmatova's epoch, but the degree of presence of different persons in the list, or even their absence, does not always reflect their weight in Akhmatova's biography. The present article is devoted to the People's Commissar of Internal Affairs, the General Commissar of State Security Genrikh Yagoda, mentioned not only in the Notebooks, but also in the Diary Pages and in Akhmatova's satirical couplets of the 1930s.